Determinan Harga Saham : EPS, DER, PBV, Inflasi dan Suku Bunga Bank Indonesia - Rahman, Faisal Riza (STIE Widya Manggala, 2023)
The decision to invest in the capital market requires various kinds of information. The information commonly used by investors is fundamental information. This study aims to analyze the relationship between Earning per Share (EPS), Debt to Equity Ratio (DER), Price to Book Value (PBV), Inflation and Bank Indonesia Interest Rates on Stock Prices. The population used in this research is the food and beverages sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2018-2021. The sample in this study used a purposive sampling technique. A sample of 22 companies for 5 years. EPS research results have a significant positive effect on stock prices. Meanwhile, DER, PBV, inflation and Bank Indonesia interest rates individually have no effect on stock prices. The coefficient of determination value of 0.986 or 98.6% means that stock prices can be explained by DER, PBV, inflation and interest rates, while the remaining 1.4% is explained by other variables outside the research model.